Current and neutron scaling for megajoule plasma focus machines - Lee, S. (IOP Publishing, 2008)
In a 2007 paper Nukulin and Polukhin surmised from electrodynamical considerations that, for megajoule dense plasma focus devices, focus currents and neutron yield Yn saturate as the capacitor energy E0 is increased by increasing the capacitance C0. In contrast, our numerical experiments show no saturation; both pinch currents and Yn continue to rise with C0 although at a slower rate than at lower energies. The difference in results is explained. The Nukulin and Polukhin assumption that the tube inductance and length are proportional to C0 is contrary to laboratory as well as numerical experiments. Conditions to achieve Yn of 1013 in a deuterium plasma focus are found from our numerical experiments, at a storage energy of 3MJ with a circuit peak current of 7.6MA and focus pinch current of 2.5 MA.